Phages for Phage Therapy: Isolation, Characterization, and Host Range Breadth - Paul Hyman (MDPI AG, 2019)
For a bacteriophage to be useful for phage therapy it must be both isolated from the environment and shown to have certain characteristics beyond just killing strains of the target bacterial pathogen. These include desirable characteristics such as a relatively broad host range and a lack of other characteristics such as carrying toxin genes and the ability to form a lysogen. While phages are commonly isolated first and subsequently characterized, it is possible to alter isolation procedures to bias the isolation toward phages with desirable characteristics. Some of these variations are regularly used by some groups while others have only been shown in a few publications. In this review I will describe (1) isolation procedures and variations that are designed to isolate phages with broader host ranges, (2) characterization procedures used to show that a phage may have utility in phage therapy, including some of the limits of such characterization, and (3) results of a survey and discussion with phage researchers in industry and academia on the practice of characterization of phages.